Development of seaweed-based bioplastic - Jacinto, Jhoanna Faye Porlit
The environmental impact of conventional plastics has driven the search for sustainable alternatives, among which seaweed-based bioplastic derived from seaweed polysaccharides as alternative and cheaper materials (e.g., food-grade agar, alginate, and semi-refined carrageenan, with glycerol as a plasticizer) was developed and characterized. A four-factor, five level Central Composite Design of Response Surface Methodology (RSM) was employed to investigate the influence of agar (0-8% w/v), alginate (0-8% w/v), carrageenan (0-8% w/v), and glycerol (5-65% w/v) concentrations on the bioplastic's physical and mechanical properties. The statistical model established significant relationships (p,0.0001) between the formulation variables and key bioplastic properties. Optimized conditions of 6.00% w/v agar, 5.444%w/v alginate, 2% w/v carrageenan, and 20% w/v glycerol yielded high-quality bioplastic with 1,000 desirability, characterized by by 1.75 x 10⁻⁹ g m m⁻² Pa⁻¹ s⁻¹ water vapor permeability, 45.62 MPa tensile strength, and 14.82 % elongation at break. Validation experiments confirmed the model's accuracy, showing negligible difference between predicted and experimental results. The optimized seaweed-based bioplastic exhibited excellent properties, including strong water vapor permeability, tensile strength, elongation, moisture content, and oxygen barrier capabilities. It also demonstrated favorable optical properties and biogradability, fully degrading in water within 21 days and in soil within 28 days, with a low microbial load suitable for food packaging. These characteristics make the bioplastic ideal for packaging perishable agro and fishery products, such as fresh vegetables, fruits, fish, shellfish, and ready-to-eat seafood, offering a sustainable alternative to conventional plastics. This research, hence, establishes seaweed-based bioplastics as a promising sustainable alternative to conventional plastics, offering superior mechanical, physical, and environmental performance.